Pharmacoeconomic analysis of first-choice antimicrobial drugs prescribed for outpatient treatment of non-severe community-acquired pneumonia - V. G. Deriushkin; A. P. Ternavskii; S. V. Gatsura (IRBIS LLC, 2021)
The study aimed to perform a pharmacoeconomic analysis of antimicrobial drugs (AMDs) prescribed for the treatment of community-acquired pneumonia (CAP) in outpatient conditions.Materials and methods. 650 medical histories of patients aged 18 to 65 years old with a diagnosis of CAP who received outpatient treatment in a larg Moscow municipal polyclinic in 2018-2019 were selected for pharmacoeconomic analysis. A model of antimicrobial drug consumption was built based on actual Algorithms of Patients' Management endorsed by the Moscow Department of Healthcare (MDH) in 2018. The analysis of the used AMPs costs in real medical practice and the simulated situation was carried out. To process the obtained results, "Statistica 13.0" software was used Results. The studied sampling of 650 medical histories included 386 (59.4%) women and 264 (40.6%) men with an average age of 39.8±16.8 years The average real clinical course cost of antimicrobial treatment calculated with a reference to the price and the percentage of total AMDs administered was worth 617.50 rubles. A comparison of the calculated average actual and simulated average AMDs course costs revealed that outpatient treatmen of CAP patients with adherence to the current MDH Algorithms would cost 394.13 rubles what would be 1.6 times more cost-effective than in the current practice.Conclusions. A course of outpatient treatment of CAP with aminopenicillins and macrolides in accordance with the actual MDH Algorithms regarding the preferences of doctors when choosing antimicrobial drugs within groups would cost on average 394.13 rubles which makes it more cost-effective as compared to real practice expenses.